Standardizing Health Outcomes for Lung Cancer. Adaptation of the International Consortium for Health Outcomes Measurement Set to the Spanish Setting - Escudero-Vilaplana, Vicente; Calles, Antonio; Collado-Borrell, Roberto; Belén Marzal-Alfaro, María; Polanco, Carlos; Garrido, Carmen; Suarez, Jorge; Ortiz, Aurora; Appierto, Marilena; Comellas, Marta; Lizán, Luis (Frontiers in Oncology, 2020)
Purpose: Lung cancer (LC) and its treatment impose a significant burden on patients' life. However, patient-centered outcomes are rarely collected during patient follow-up. Filling this gap, the International Consortium for Health Outcomes Measurement (ICHOM) developed a standard set of variables for newly diagnosed LC patients. In order to facilitate the use of this standard set, the project aims to adapt it to the Spanish setting. Methods: The variables (instrument and periodicity) to be included in Spanish standard set were selected through consensus during 4 nominal groups (13 oncologists, 14 hospital pharmacists, 4 hospital managers and 3 LC patients), under the supervision of a Scientific Committee (1 oncologist, 3 hospital pharmacists, 2 LC patients advocates). Results: The variables agreed upon included: (1) case-mix: demographic [age, sex, education and social-family support], clinical [weight loss, smoking status, comorbidities (Charlson index), pulmonary function (FEV-1)], tumor [histology, clinical, and pathological stage (TNM), EGFR, ALK, ROS-1, PD-L1] and treatment factors [intent and completion] and (2) outcomes: degree of health [performance status (ECOG) and quality-of-life (EQ-5D, LCSS)], survival [overall survival and cause of death], quality of death [place of death, end-of-life care and palliative care, death aligned with living will], treatment complications, and others [date of diagnosis and treatment initiation, productivity loss (sick leave)]. Conclusion: The adaptation of ICHOM standard set to the Spanish setting pave the way to standardize the collection of variables in LC.